Enhanced Insulin Signaling Through Its Receptor Is Needed for the Development of Hyperuricemia in Humans - Haykal, Rasha (J Endocr Soc, 2021)
Background: There is an association between insulin resistance (IR) and hyperuricemia but the direction of causalityand mechanisms are unclear. In obesity and lipodystrophy, IR is “selective”, with lack of insulin signalingcausing hyperglycemia, but enhanced insulin signaling causing dyslipidemia and possibly hyperuricemia. Rare human conditions exist in which there is extreme, non-selective, IR impairing all insulin signalingpathways (e.g. mutations of the insulin receptor, INSR). We hypothesized that hyperinsulinemia withenhanced signaling through the insulin receptor causes hyperuricemia in selective IR, whereas lack ofinsulin signaling through its receptor despite hyperinsulinemia results in normal uricemia in non-selective IR. Method: Cross-sectional retrospective analysis comparing fasting insulin and serum uric acid in patients withsevere IR that was either selective (due to lipodystrophy) or non-selective (due to INSR mutation orautoantibody to the insulin receptor). Visits were chosen based on availability of serum uric acid andinsulin. If multiple visits were available, the visit with the highest insulin value was chosen. Results: We analyzed data of 68 patients with selective IR and 14 patients with non-selective IR. Fasting seruminsulin median [interquartile range] was 23.4 [14, 53] mcU/mL in selective IR vs 215 [73.7, 604] in non-selective IR, p <0.0001. Serum uric acid was 4.8 [2, 6] mg/dL in selective IR vs 3.5 [2, 4] in non-selectiveIR, p=0.0003. Conclusion: Patients with selective IR due to lipodystrophy had elevated serum uric acid, consistent with thehyperuricemia seen in selective IR caused by obesity. By contrast, patients with non-selective IR hadlower serum uric acid despite more severe IR as evidenced by almost 10-fold higher fasting insulin. These observations are consistent with a model in which enhanced insulin signaling through its receptorleads to hyperuricemia in post-receptor IR. Further studies are needed to understand the mechanism bywhich insulin leads to hyperuricemia.